Visi, Misi dan Sifat Pendidikan Islam - Ella Juniani; Musliati Musliati; Nadila Kirani; Mardinal Tarigan; Marzuki Marzuki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Without a doubt, everyone is naturally inclined to learn. As a result, no matter the situation, a person picks up knowledge from the world around them. However, what about Islamic education? In comparison to other educational institutions, Islamic education unquestionably occupies a better and more honorable position. The causes are evident. In order for Islamic education to remain intense and relevant, its sources and teaching strategies are the Al-Qur'an and the Sunnah of the Prophet Muhammad SAW. As an Islamic educational institution, it is crucial to promote a learning system that can foster critical and creative thinking, producing smart individuals who can broaden the scope of the religion. Keywords: vision, mission, nature of Islamic education